Cutaneous manifestations in obese patients and non-obese controls in a tertiary care centre: a case-control study - Chekuri, Raghuveer; Mohamed, Thameena (International Journal of Research in Dermatology, 2019)
Background: Obesity has emerged as one of the most serious public health concerns in the 21st century. It is responsible for varied changes in structure and function of different components of skin. Skin care of obese patients deserves particular attention, not only because of high prevalence of cutaneous alteration but mainly because many of these disorders are preventable and could be treated, improving patient’s quality of life. Methods: Two hundred patients with BMI ≥30 kg/m2 and two hundred age and sex matched controls (BMI: 18.5-24.9 kg/m2) were included in this study. Results: Compared to the control group, obese patients were having higher prevalence of various skin conditions of which most common were acanthosis nigricans, acrochordons, striae distensae, frictional hyperpigmentation and infections. Conclusions: There is increased incidence and severity of cutaneous manifestations like acanthosis nigricans, acrochordons, striae distensae, frictional hyperpigmentation and infections in obese patients than control subjects. These can be used as markers for the early detection of various components of metabolic syndrome.